2011
DOI: 10.1037/a0025806
|View full text |Cite
|
Sign up to set email alerts
|

Internet-based maintenance treatment for patients with eating disorders.

Abstract: The sustainability of treatment effects is a major challenge in clinical practice. As in most other mental disorders, patients with eating disorders frequently expedence relapses following treatment termination. This calls for feasible maintenance strategies that can be implemented in clinical routine at reasonable cost and effort for both treatment providers and patients. This article introduces an Intemet-based intervention for maintenance support of patients with bulimia nervosa (BN) and related eating diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 24 publications
0
46
0
Order By: Relevance
“…20 The efficacy of two more comprehensive technology-enhanced programs in the maintenance treatment of bulimia nervosa and related EDNOS is currently investigated in ongoing RCTs. Gulec et al 21 study a 16-weeks program that uses a similar monitoring component as described above in order to track participants impairment throughout participation and provide tailored supportive feedback at regular intervals. In addition, participants communicate among one another and with a clinician through online forums and chat sessions that are delivered in group format (weekly) and individual format (on demand).…”
Section: Relapse Prevention and Maintenance Treatmentmentioning
confidence: 98%
See 2 more Smart Citations
“…20 The efficacy of two more comprehensive technology-enhanced programs in the maintenance treatment of bulimia nervosa and related EDNOS is currently investigated in ongoing RCTs. Gulec et al 21 study a 16-weeks program that uses a similar monitoring component as described above in order to track participants impairment throughout participation and provide tailored supportive feedback at regular intervals. In addition, participants communicate among one another and with a clinician through online forums and chat sessions that are delivered in group format (weekly) and individual format (on demand).…”
Section: Relapse Prevention and Maintenance Treatmentmentioning
confidence: 98%
“…Preliminary evidence points to the feasibility and acceptability of the intervention. 21 The potential of a manualized CBT-oriented approach in the aftercare of bulimia nervosa is studied in another trial. 22 The 9-month intervention includes 11 sessions.…”
Section: Relapse Prevention and Maintenance Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…These include: (a) greater potential for the integration of acquired skills in daily life due to an emphasis on the patient's active role in self-help treatment, (b) elimination of waiting periods between acute and continuation treatment, (c) access to the programs on a 24/7 basis, and (d) lower costs compared to face-to-face treatments. Several studies have shown promising results with delivering continuation phase treatments over the Internet [16,17,18,19,20,21]. However, to our knowledge, all published studies evaluating the use of this approach to maintain inpatient treatment gains [16,17,20] used only nonrandomized designs.…”
mentioning
confidence: 93%
“…Some maintenance approaches have also been introduced using technology to maintain treatment gains and to prevent relapse. [38][39][40][41] Overall, the findings are promising with respect to feasibility and efficacy of such interventions, but there is a clear need for further research as only very few adequately powered randomized controlled trials (RCTs) have been completed so far. 42,43 A relapse prevention program using short message service (SMS) and text messaging technology proved feasible 38 and efficacious 39 among patients with BN and related EDNOS.…”
Section: Introductionmentioning
confidence: 94%